Women's labor force participation - Anne E. Winkler (IZA World of Labor, 2022)
Female labor force participation is mainly driven by the value of their market wages versus the value of their non-market time. Labor force participation varies considerably across countries. To understand this international variation, it is important to further consider differences across countries in institutions, non-economic factors such as cultural norms, and public policies. Such differences provide important insights into what actions countries might take to further increase women's participation in the labor market.
Keywords: J2; J16; J18; 330; gender; women; labor force participation; family policies